(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Artificial intelligence (AI), in straightforward terms, can be characterized as the securing of insight by PCs or machines to perform assignments that typically require human knowledge.Materials and methods: A survey based questionnaire was done to study the knowledge about artificial intelligence and its uses among dental students. A total questionnaire of 15 questions were collected by google form app. SPSS statistical analysis was done. A total of 100 participants participated in this survey. Result: The results were collected and data were analysed. 84% of the participants were aware of the artificial intelligence and its uses among dental students. The difference of the result is statistically significant (p<0.05). Conclusion: This study concludes that the majority of the participants were aware of artificial intelligence and its uses.